Characterization of Pyrolysis Kinetics of Continental Shale: Comparison and Enlightenment of the Parallel Reaction Model and the Overall Reaction Model - Jiang, Jun; Li, Jijun; Wang, Yiwei; Chen, Xudong; Wang, Min; Lu, Shuangfang; You, Hang; Zheng, Ketao; Yan, Chenxu; Li, Zhongcheng; Yu, Limin (Frontiers in Earth Science, 2022)
A total of nine immature–low maturity oil shale samples from Fushun and Maoming, the main oil shale producing areas in China, and three mature shale samples from the Jiyang Depression, China, were selected for use in hydrocarbon generation thermal simulation experiments in an open system and a closed system. The parallel first–order reaction kinetic model and the overall nth–order reaction kinetic model were used to calibrate the pyrolysis kinetic parameters of the samples. This comparative study revealed following conclusion. The generation period of the gaseous hydrocarbons (C1–5) was the longest, and the generation period of the heavy hydrocarbon (C14+) was the shortest. The activation energy of the hydrocarbon generation reaction was closely related to the maturity of the organic matter, i.e., the higher the maturity of the sample, the higher the activation energy of the reaction, which indicates that oil shale/shale oil conversion requires higher temperature conditions. The parallel first–order reaction model regards the hydrocarbon generation reaction as a series of first–order reactions, and it has a better fitting effect for the longer hydrocarbon generation period reactions, such as generating gaseous hydrocarbons (C1–5) and light components (C6–14) from organic matter. The overall nth–order reaction treats the reaction as a nth–order reaction, and the nth–order reaction has a better fitting effect for reactions with a narrow hydrocarbon generation window, such as generating heavy components from organic matter. In the process of generating hydrocarbons from organic matter, the order of the reaction is the sum of the orders of the sub–reactions; and the more hydrocarbon–generating parent material, the larger the order of the reaction corresponding to the hydrocarbon–generating reaction. The reaction order of the generation of different hydrocarbons from organic matter is as follows: generation of gaseous hydrocarbons from organic matter > generation of light hydrocarbons from organic matter > generation of heavy hydrocarbons from organic matter.